2018
DOI: 10.1007/s40430-018-1301-7
|View full text |Cite
|
Sign up to set email alerts
|

The rheological behaviour of a water-soluble polymer (HEC) used in drilling fluids

Abstract: The rheological properties of drilling fluids have been always considered as critical aspects to the success of drilling operations; in this fact, the control of these properties was of paramount importance. In this paper, the rheological behaviour of a water-soluble polymer, namely hydroxyethyl cellulose (HEC) used in drilling fluids, was investigated. Steady-state shear rheology and frequency experiment were carried out on the sample at different concentrations ranging from 0.1 to 1.2 wt% and constant temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The results show that the solutions are approximately Newtonian at low shear rates, followed by a shear thinning behaviour at high shear rates. Detailed explanation of these results can be found in Ouaer and Gareche [44]. The flow curves of HEC solutions are well fitted by the well-known Cross model [10], which is expressed by:…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 56%
See 2 more Smart Citations
“…The results show that the solutions are approximately Newtonian at low shear rates, followed by a shear thinning behaviour at high shear rates. Detailed explanation of these results can be found in Ouaer and Gareche [44]. The flow curves of HEC solutions are well fitted by the well-known Cross model [10], which is expressed by:…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 56%
“…A water-soluble polymer considered as a cellulose derivative, namely hydroxyethyl cellulose (HEC) of high molecular weight (~ 9.5 × 10 5 g/mol), was used as an additive to the bentonite suspensions for controlling the rheological behaviour of these suspensions. Detailed description of the HEC sample properties and uses can be found in Ouaer and Gareche [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] Hydroxyethyl cellulose can be used as a thickener and a fluid loss reducer in drilling operations. [13] However, there are limits to application of hydroxyethyl cellulose at high temperatures due to the existence of ether bonds. [14] And the use of hydroxyethyl cellulose alone in the drilling fluid generally does not exceed 110℃.…”
Section: Introductionmentioning
confidence: 99%
“…Koda et al [ 20 ] have compared the water retention capacity among MC, HeC, and hydroxypropyl cellulose (HpC) by using the compression method and differential scanning calorimetry measurements and concluded that the capacity of hydroxyethyl cellulose is the strongest. Ouaer et al [ 21 ] have determined the intrinsic viscosity and the critical overlap concentration of HeC molecules in aqueous solution. However, these studies were carried out at room temperature ca.…”
Section: Introductionmentioning
confidence: 99%